2017
DOI: 10.3989/scimar.04651.17a
|View full text |Cite
|
Sign up to set email alerts
|

Variability patterns of epibenthic microalgae in eastern Tunisian coasts

Abstract: Summary: Epiphytic microalgae were monitored on various substrates of seagrass and macroalgae and in the water column for one year (from March 2013 to March 2014) in Oued Lafrann along the eastern coast of Chebba (Tunisia) with a focus on the distribution patterns of the epibenthic toxic dinoflagellates Ostreopsis cf. ovata, Prorocentrum lima and Coolia monotis. Microalgae assemblages were dominated by diatoms and dinoflagellates both in the water column and on vegetation. High concentrations of epiphytic toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…In our study area, the Gulf of Gabès (Fig. 1), located in the South-eastern Mediterranean Sea (Southeast of Tunisia) and sheltering Kerkennah and Djerba islands and Boughrara and El Bibane lagoons, C. monotis has been recorded in the water column (Abdennadher et al 2020), attached to the sediment and the adjacent water "biofilm" (Loukil-Baklouti et al 2018) and on various substrates (magnoliophytes and macroalgae) (Moncer et al 2017).…”
Section: Cell Isolationmentioning
confidence: 99%
“…In our study area, the Gulf of Gabès (Fig. 1), located in the South-eastern Mediterranean Sea (Southeast of Tunisia) and sheltering Kerkennah and Djerba islands and Boughrara and El Bibane lagoons, C. monotis has been recorded in the water column (Abdennadher et al 2020), attached to the sediment and the adjacent water "biofilm" (Loukil-Baklouti et al 2018) and on various substrates (magnoliophytes and macroalgae) (Moncer et al 2017).…”
Section: Cell Isolationmentioning
confidence: 99%
“…The movement of the water can thus cause a stirring of the leaves allowing the displacement of the epiphyte species in the water column and that can explain their frequent observations in REPHY samples. (Moncer et al, 2017) reported that concentrations of P. lima on Posidonia oceanica leaves and in water column were significantly correlated. (Richlen & Lobel, 2011) suggested that the species, being a swimming dinoflagellate that can even be affected by low water motion conditions, might move from one compartment to another.…”
Section: Discussionmentioning
confidence: 99%
“…ovata, P. lima, and C. monotis in the north of Sfax coasts (Chebba) in different compartments (seagrasses, macroalgae, and water column). A significant resuspension of these species from macrophytes to water column was noted (Boisnoir et al, 2019;Mangialajo et al, 2017;Moncer et al, 2017). Otherwise, (Loukil et al, 2017) showed that the presence of potentially toxic species within the shellfish could originate from the sediment or the biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…In general, modern macroalgal species are characteristically composed mainly of calcareous Rhodophyta and non-calcified Ochrophyta, whereas microalgal epiphytes usually include diatoms, dinoflagellates and cyanobacteria in declining relative abundance (Piazzi et al, 2016;Agawin et al, 2017). Similarly, the modern phytoplankton assemblages are mainly composed of diatoms and dinoflagellates (Moncer et al, 2017), while the water column near Cabrera is known to harbour a great abundance of pico and nanoplankton, dinoflagellates, coccolitophorids and diatoms (Vives, 1993). We suggest that seagrass, possibly in association with rhodophytes, is the main source of the couplet lutein-zeaxanthin, as it is the most abundant carotenoid in live P. oceanica tissues (Casazza & Mazella, 2002).…”
Section: Seagrass Phototrophic Communitymentioning
confidence: 99%